Is there an error in this textbook about Peano Arithmetic? - logic

I encountered this doubt in an online intro-logic open course offered by Stanford Uni.
Under the section 9.4 of this textbook here: http://logic.stanford.edu/intrologic/secondary/notes/chapter_09.html
It says:
The axioms shown here define the same relation in terms of 0 and s.(where the functional constant letter s below represents the successor function, e.g. s(0)=1, s(1)=2, s(2)=3 )
∀x.same(x,x)
∀x.(¬same(0,s(x)) ∧ ¬same(s(x),0))
∀x.∀y.(¬same(x,y) ⇒ ¬same(s(x),s(y)))
As my understanding, :
The first sentence says two identical numbers are same. The second and third sentences are used to define what is not same.
The second says no successor of any number is same to 0.
The third says if two numbers are not the same, then their successors are not same. For example, if 1≠3, then 2≠4.
However, I think the third sentence should be bi-conditional because, if I'm not wrong, the definition didn't cover the instance where the number being testified are smaller than the given number,otherwise it is possible to say if 2≠4, then 1=3.
So I wondered is this an error in text book or there's something wrong of my reasoning.

There is no error in this text book. While the statement does hold in both directions, there is no need to state it as an axiom since the other direction follows from the functional property of the successor function and the three axioms listed in the textbook.
A formal proof would involve the axioms that define the successor function. Someone more accustomed to the use of automated provers or just a good student of logic might be able to complete such a formal proof.
Here is just a sketch of a proof. It uses the symbol "=" to denote term equality, i.e. u=v means u and v are syntactically identical terms written using the symbols 0 and s(). Also "u<v" means that u and v are both ground terms and u has strictly less applications of s() than v.
Suppose
∀x.∀y.(¬same(s(x),s(y)) ⇒ ¬same(x,y))
does not hold, then there exist some terms x0 and y0 such that
same(x0,y0) and ¬same(s(x0),s(y0)).
Since s(x0) is a function, it follows from ¬same(s(x0),s(y0)) and ∀x.same(x,x) that x0 and y0 are two different terms. First let us consider the case when x0 < y0, then y0 = s(...s(x0)) where there are n applications of s() and n > 0. The other case when y0 < x0 can be handled similarly.
Substituting s(...s(x0)) for y0 in same(x0,y0) we get same(x0,s(...s(x0))).
Also x0 = s(...s(0)) where there are m applications of s() for some nonnegative integer m. Using the third axiom in the direction provided we can say that if same(s(u),s(v)) then same(u,v). Thus from same(x0,s(...s(x0))) we can "strip" m applications of s() to obtain
same(0,s(...s(0))) where there are n applications of s() in the second argument. This contradicts the second axiom. Q.E.D.

Related

Coq `simpl` reduces `S n + m` to `S(n + m)` for free?

I'm just beginning to learn Coq via software foundations. One of the homework Theorems (with my successful proof elided) in Induction.v is:
Theorem plus_n_Sm : forall n m : nat,
S (n + m) = n + (S m).
Proof.
(* elided per request of authors *)
Qed.
Later, I noticed that the following similar "leftward" statement comes for free with the built-in tactic .simpl:
Example left_extract : forall n m : nat, S n + m = S (n + m).
Proof.
intros. simpl. reflexivity.
Qed.
I've perused the documentation and haven't been able to figure out why .simpl gives us one direction "for free" but the other direction requires a user-supplied proof. The documentation is over my head at this very early point in my learning.
I guess it has something to do with left-ness being built-in and right-ness being not, but the propositions seem to my childlike eyes to be of equal complexity and subtlety. Would someone be so kind as to explain why, and perhaps give me some guidance about what is going on with .simpl?
Why should I NOT be surprised by my finding?
What other good things can I expect from .simpl, so it surprises me less and so I can eventually predict what it's going to do and rely on it?
What's the best way to wade through the theory -- unfolding of iota reductions and what not -- to focus on the relevant bits for this phenomenon? Or do I have to learn all the theory before I can understand this one bit?
I believe your surprise stems from the fact that you are accustomed to think of addition as a primitive concept. It is not, it is a function that has been defined and other primitive concepts are used to explain its behavior.
The addition function is defined by a function with a name written with letters (not the + symbol) in a way that looks like this:
Fixpoint add (n m : nat) : nat :=
match n with
| 0 =>
| S p => S (add p)
end.
You can find this information by typing
Locate "_ + _".
The + notation is used for two functions, only one of them can be applied on numbers.
Coming back to the add function, its very description explains that add 0 m computes to m and add (S n) m computes to S (add m n), but it does not say anything when the second argument has the form S m, it is just not written anywhere. Still the theory of Coq makes it possible to prove the fact.
So the equality that is given for free comes directly from the definition of addition. There are a few other equality statements that are natural to the human eye, but not given for free. They can just be proved by induction.
Would it be possible to design the Coq system in such a way that both equality statements would be given for free? The answer is probably yes, but the theory must be designed carefully for that.

Does SKS equal SKK?

Context
I started teaching myself lambda calculus last night and I am trying to determine if what I understand so far is correct.
Understanding
SKK is equivalent to the Identity combinator, I.
Where L stands for lambda:
S = LxLyLz((xz)(yz))
K = LxLy(x)
K essentially takes the next 2 (lambda) terms and gives back the first of those. S seems a little more complicated in the untyped lambda calculus.
My Interpretation
SK(any-lambda-term) is also equivalent to I.
I.e. the application of the application of S to K to Any-lambda-term is equivalent to the Identity combinator:
((S K)(Any)) = I = S K K = ((S K)(K))
I am using the convention of “left-association” in my above notation, if that helps (And I tried to make that clear in the 4th term above with parentheses. Everything I have read so far seems to use this convention).
Reasoning
S K = LyLz((K z)(y z))
The next lambda term will be substituted for y, let the term be Y.
S K Y = Lz((K z)(Y z))
(Y z) is the application of Y to z, also a lambda term.
(K z)returns the constant function that returns z, given another term input: (Y z).
Is my interpretation true? If not, can you provide an explanation? I would greatly appreciate it. Particularly if a sort of order of operations can be explained—I regularly find myself confused when considering when to evaluate. Perhaps that will be refined with practice.
Your intuition is correct, but an intuition proves nothing (alas...)
So, how can we prove your statement? Simply by showing that SKK and SKS have the same behaviour. "Behaviour" is an informal notion, which is formally capture by "semantics": if SKK and SKS are equals, then they should always reduce to the same term, according to the SKI-calculus semantics.
Now, there is a deep question, which is: what are the SKI-calculus? Actually, there is not a single way to answer that. What you implicitly do in your question is that you express SKI in terms of λ terms and you rely on the semantics of the λ calculus. This is absolutly correct. An other way to do it could have been to define directly SKI semantics. For instance, if you look at the wikipedia page, you can see that the semantics are not defined with lambda terms (and the fact that it correspond to lambda term is a (nice and expected) side effect). In the rest of this answer, I'll take the same approach as you do, and convert SKI terms in λ terms. A good exercise for you is to redo the proof, using the proper SKI semantics.
So, let formalize your question: your question is whether, for any SKI term t, SKKt = SKSt? Well... Let's see.
SKKt is encoded as (λx.λy.λz.(xz)(yz))(λx.λy.x)(λx.λy.x)t in the λ-calculus. We now just have to reduce it to a normal form (I detail every step, each time I reduce the leftmost λ, even tho it is not the fastest strategy):
(λx.λy.λz.(xz)(yz))(λx.λy.x)(λx.λy.x)t
= (λy.λz.((λx.λy.x)z)(yz))(λx.λy.x)t
= (λz.((λx.λy.x)z)((λx.λy.x)z))t
= ((λx.λy.x)t)((λx.λy.x)t)
= (λy.t)((λx.λy.x)t)
= t
So, the encoding of SKKt in the λ calculus reduces to t (as a sidenote, we just proved that SKK is equivalent to I here). To conclude our proof, we have to reduce SKSt and see whether it also reduces to t.
SKSt is encoded as (λx.λy.λz.(xz)(yz))(λx.λy.x)(λx.λy.λz.(xz)(yz))t. Let reduce it. (I don't detail as much this time)
(λx.λy.λz.(xz)(yz))(λx.λy.x)(λx.λy.λz.(xz)(yz))t
= ((λx.λy.x) t)((λx.λy.λz.(xz)(yz)) t))
= (λy.t)((λx.λy.λz.(xz)(yz)) t))
= t
Hurrah! It also reduce to t, so indeed, SKS and SKK are equivalent. It seems that the third combinator is not important: that as soon as you have SK?, it is equivalent to I. As an exercise, you can easily prove it (same strategy, if it is the case, then for any terms t and s, SKts = s). As mentionned above, an other good exercise is to redo the proof without using the λ semantics, but the proper SKI semantics.
Finally, my answer should raise a new question to you: we have two semantics, one that encodes SKI terms into λ terms, and one that does not. The question you may have is: are the two semantics equivalent? What does it mean for two semantics to be equivalent? If you are only starting to teach yourself λ calculus, it may be a bit early to try to answer those questions right now, but you can keep it in a corner of your head for when you'll get more familiar with formal languages.

How to demonstrate a set is decidible, semi-decidible or not semi-decidible?

I have been asked to prove if the following set is decidible, semi-decidible or not semi-decidible:
In other words, it is the set of inputs such that exists a Turing Machine encoded with the natural y with input p that returns its input.
Consider the set K as the set of naturals such that the Turing machine encoded with x and input x stops. This is demonstrated to be a non-decidible set.
I think that what I need is to find a reduction of K to L, but I don't know how to prove that L is decidible, semi-decidible or not semi-decidible.
L may not look decidable at first glance, because there is this nasty unbounded quantifier included, which seems to make necessary a possibly infinite search when you look for a y satisfying the condition for a specific p.
However, the answer is much simpler: There is a turing machine M which always returns its input, i.e. M(p) = p holds for all p in the considered language. Let y be a code of M. Then you can use this same y for all p, showing that L contains all words of the language. Hence L is of course decidable.
In fact, this is an example to demonstrate the principle of extensionality (if two sets have the same elements and one is decidable, then the other is decidable too, even if it doesn't look so).

How the Symbolic State Exploration works in Symbolic Model Checking

The following algorithm is a rough sketch of model checking with Computational Tree Logic (CTL):
It is stated that:
The model-checking problem for CTL is to verify for a given transition system TS and CTL formula Φ whether TS |= Φ... The basic procedure for CTL model checking is rather straightforward:
the set Sat(Φ) of all states satisfying Φ is computed recursively, and
it follows that TS |= Φ if and only if I ⊆ Sat(Φ)
where I is the set of initial states of TS...
The recursive computation of Sat(Φ) basically boils down to a bottom-up traversal of the parse tree of the CTL state formula Φ.
So you essentially (from my understanding), you provide the system with a CTL formula Φ, which is a parse tree, and then it searches through the states, and through the CTL parse tree, and checks if any state satisfies Φ.
The question is:
In the Sat(Φ) method, roughly what happens (the symbolic stuff). They say (2) below, where S is states and A is atomic propositions. Wondering how they actually check the states, given that the program isn't actually running. It is (at least I think) Symbolic Model Checking. Wondering if one could explain roughly how the state checking works. It seems like some sort of input generation has to occur, but at the same time I'm thinking maybe it shouldn't occur.
The reason for it being hard to understand for me is this. Say one of the assertions is for a function addTricky(x, y) which is implemented like this:
function addTricky(x, y) {
if (y >= 1) return 3
return x + y
}
Then I would have a Boolean expression in some logic that says "before addTricky : z = 0. after z = addTricky(x, y) : y >= 1 -> z = 3 ; y < 1; z = x + y".
Basically trying to get at the question of patterns. If Sat(Φ) is doing basically what I just did in that Boolean expression, I wonder if it ever calls/invokes the function addTricky, or if it can do it all symbolically somehow. I don't see how that works yet, wondering if the basics of how the symbolic execution works could be explained a bit. To me I keep imagining it doing some sort of Unit Testing, like plugging in addTricky(1, 1) for example, and checking all the possibilities. Maybe that is "explicit state exploration" vs. symbolic exploration, not sure.
Thank you so much for the help!
(1) For each node of the parse tree, i.e., for each subformula Ψ of Φ, the set Sat(Ψ) of states is computed for which Ψ holds.
(2) Sat(a) = {s ∈ S | a ∈ L(s)}, for any a ∈ A
I think there are two parts to your question: 1) How to go from a software function to a transition system and 2) how is the transition system used to check satisfaction.
1) A transition system is basically an extension of a finite state automaton. If you have a function like you described, you first need to transform it into a transition system. This can be done, for example, by introducing states for each executable line of your code, and transitions between those states that follow the conditions of your code. At the transition system level you do not have the concept of function call, therefore you need to take care of this during the translation e.g., by in lining function definitions. This step is independent on how you verify the transition system. As you can imagine this can lead to pretty large transition systems.
There are other approaches, that are not based on transition systems, that simulate the execution of the program and collect symbolic constraints along the way. Symbolic execution is such an example.
2) Let's say that you inline your addTricky function and get something along these lines
L0: z=0
if (y>=1)
L1: z=3
else
L2: z=x+y
A possible TS is:
(L0: z=0) --[y >= 1]--> (L1: z=3)
|
[y<1]
\/
(L2: z=x+y)
You have 3 executable statements and this leads to a TS whose symboiic states (S) are:
L0: Z=0; X=?; Y=?
L1: Z=3; X=?; Y>=1
L2: Z=X+Y; X=?; Y<1
where ? means any value. The power of this approach is that you can compactly represent all the values of X and Y in a single symbolic state.

Flattening quantification over relations

I have a Relation f defined as f: A -> B × C. I would like to write a firsr-order formula to constrain this relation to be a bijective function from A to B × C?
To be more precise, I would like the first order counter part of the following formula (actually conjunction of the three):
∀a: A, ∃! bc : B × C, f(a)=bc -- f is function
∀a1,a2: A, f(a1)=f(a2) → a1=a2 -- f is injective
∀(b, c) : B × C, ∃ a : A, f(a)=bc -- f is surjective
As you see the above formulae are in Higher Order Logic as I quantified over the relations. What is the first-order logic equivalent of these formulae if it is ever possible?
PS:
This is more general (math) question, rather than being more specific to any theorem prover, but for getting help from these communities --as I think there are mature understanding of mathematics in these communities-- I put the theorem provers tag on this question.
(Update: Someone's unhappy with my answer, and SO gets me fired up in general, so I say what I want here, and will probably delete it later, I suppose.
I understand that SO is not a place for debates and soapboxes. On the other hand, the OP, qartal, whom I assume is the unhappy one, wants to apply the answer from math.stackexchange.com, where ZFC sets dominates, to a question here which is tagged, at this moment, with isabelle and logic.
First, notation is important, and sloppy notation can result in a question that's ambiguous to the point of being meaningless.
Second, having a B.S. in math, I have full appreciation for the logic of ZFC sets, so I have full appreciation for math.stackexchange.com.
I make the argument here that the answer given on math.stackexchange.com, linked to below, is wrong in the context of Isabelle/HOL. (First hmmm, me making claims under ill-defined circumstances can be annoying to people.)
If I'm wrong, and someone teaches me something, the situation here will be redeemed.
The answerer says this:
First of all in logic B x C is just another set.
There's not just one logic. My immediate reaction when I see the symbol x is to think of a type, not a set. Consider this, which kind of looks like your f: A -> BxC:
definition foo :: "nat => int × real" where "foo x = (x,x)"
I guess I should be prolific in going back and forth between sets and types, and reading minds, but I did learn something by entering this term:
term "B × C" (* shows it's of type "('a × 'b) set" *)
Feeling paranoid, I did this to see if had fallen into a major gotcha:
term "f : A -> B × C"
It gives a syntax error. Here I am, getting all pedantic, and our discussion is ill-defined because the notation is ill-defined.
The crux: the formula in the other answer is not first-order in this context
(Another hmmm, after writing what I say below, I'm full circle. Saying things about stuff when the context of the stuff is ill-defined.)
Context is everything. The context of the other site is generally ZFC sets. Here, it's HOL. That answerer says to assume these for his formula, wich I give below:
Ax is true iff x∈A
Bx is true iff x∈B×C
Rxy is true iff f(x)=y
Syntax. No one has defined it here, but the tag here is isabelle, so I take it to mean that I can substitute the left-hand side of the iff for the right-hand side.
Also, the expression x ∈ A is what would be in the formula in a typical set theory textbook, not Rxy. Therefore, for the answerer's formula to have meaning, I can rightfully insert f(x) = y into it.
This then is why I did a lot of hedging in my first answer. The variable f cannot be in the formula. If it's in the formula, then it's a free variable which is implicitly quantified. Here's the formula in Isar syntax:
term "∀x. (Ax --> (∃y. By ∧ Rxy ∧ (∀z. (Bz ∧ Rxz) --> y = z)))"
Here it is with the substitutions:
∀x. (x∈A --> (∃y. y∈B×C ∧ f(x)=y ∧ (∀z. (z∈B×C ∧ f(x)=z) --> y = z)))
In HOL, f(x) = f x, and so f is implicitly, universally quantified. If this is the case, then it's not first-order.
Really, I should dig deep to recall what I was taught, that f(x)=y means:
(x,f(x)) = (x,y) which means we have to have (x,y)∈(A, B×C)
which finally gets me:
∀x. (x∈A -->
(∃y. y∈B×C ∧ (x,y)∈(A,B×C) ∧ (∀z. (z∈B×C ∧ (x,z)∈(A,B×C)) --> y = z)))
Finally, I guess it turns out that in the context of math.stackexchange.com, it's 100% on.
Am I the only one who feels compulsive about questioning what this means in the context of Isabelle/HOL? I don't accept that everything here is defined well enough to show that it's first order.
Really, qartal, your notation should be specific to a particular logic.
First answer
With Isabelle, I answer the question based on my interpretation of your
f: A -> B x C, which I take as a ZFC set, in particular a subset of the
Cartesian product A x (B x C)
You're sort of mixing notation from the two logics, that of ZFC
sets and that of HOL. Consequently, I might be off on what I think you're
asking.
You don't define your relation, so I keep things simple.
I define a simple ZFC function, and prove the first
part of your first condition, that f is a function. The second part would be
proving uniqueness. It can be seen that f satisfies that, so once a
formula for uniqueness is stated correctly, auto might easily prove it.
Please notice that the
theorem is a first-order formula. The characters ! and ? are ASCII
equivalents for \<forall> and \<exists>.
(Clarifications must abound when
working with HOL. It's first-order logic if the variables are atomic. In this
case, the type of variables are numeral. The basic concept is there. That
I'm wrong in some detail is highly likely.)
definition "A = {1,2}"
definition "B = A"
definition "C = A"
definition "f = {(1,(1,1)), (2,(1,1))}"
theorem
"!a. a \<in> A --> (? z. z \<in> (B × C) & (a,z) \<in> f)"
by(auto simp add: A_def B_def C_def f_def)
(To completely give you an example of what you asked for, I would have to redefine my function so its bijective. Little examples can take a ton of work.)
That's the basic idea, and the rest of proving that f is a function will
follow that basic pattern.
If there's a problem, it's that your f is a ZFC set function/relation, and
the logical infrastructure of Isabelle/HOL is set up for functions as a type.
Functions as ordered pairs, ZFC style, can be formalized in Isabelle/HOL, but
it hasn't been done in a reasonably complete way.
Generalizing it all is where the work would be. For a particular relation, as
I defined above, I can limit myself to first-order formulas, if I ignore that
the foundation, Isabelle/HOL, is, of course, higher-order logic.

Resources